The reciprocal jaw-muscle reflexes elicited by anterior- and back-tooth-contacts-a perspective to explain the control of the masticatory muscles - Lauri Vaahtoniemi (Nature Publishing Group, 2020)
Abstract Aims Tooth-contact sensations are considered essential to boost jaw adductor muscles during mastication. However, no previous studies have explained the importance of the inhibitory reflex of human anterior-tooth (ANT)-contacts in mastication. Here I present the "reciprocal reflex-control-hypothesis" of mammalian mastication. Subjects and setting of the study I demonstrate the hypothesis with the live kinematics of free jaw-closures as inferred from T-Scan recordings of dental patients. Results The jaw-closures started with negligible force, predominantly with ANT-contacts (the AF-bites). The first ANT-contact inhibited the first kinematic tilt of the mandible, whereas the bites starting from a back-tooth (BAT)-contact (the BF-bites) accelerated the first tilt. The second tilt established a low-force static tripod of the ANT- and bilateral BAT-contacts for a fixed mandible-maxilla relation. Thereafter, semi-static bite force increased rapidly, relatively more in the BAT-area. Discussion and Conclusions In the vertical-closure phase of chewing, the primate joint-fulcrum (class 3 lever) conflicts with the food-bolus-fulcrum in the BAT-area (class 1 lever). The resilient class 3 and 1 lever systems are superseded by an almost static mechanically more advantageous class 2 lever with a more rigid fulcrum at the most anterior ANT-contact. For humans, the class 2 levered delivery of force also enables forceful horizontal food grinding to be extended widely to the BAT-area.